Efektivitas Pelayanan Ketenagalistrikan melalui Aplikasi PLN Mobile dalam Menangani Keluhan - Alya Nur Faridah; Riza Hernawati (UNISBA Press, 2022)
Abstract. Service is an important thing in the implementation of public services. In this pandemic period, more services are provided through digital-based applications than conventionally, where this is an adaptation of the changes that are happening at this time. In Article 1 Chapter 1 of Law N0. 25 of 2009 states that public services are activities or series of activities in the context of fulfilling service needs in accordance with laws and regulations for every citizen and resident for services, goods and or administrative services provided by public service providers. PT. PLN has an application service in handling complaints, namely the PLN Mobile application. Services through the application launched by PT. PLN, namely